Association of serum vaspin, apelin, and visfatin levels and stroke risk in a Chinese case-control study. Issue 12 (26th March 2021) - Yu, Dalin; Huang, Bin; Wu, Bin; Xiao, Jun
Abstract : Abstract: Adipose tissue acts as an active endocrine organ secreting a number of adipokines and may be involved in biological mechanism of stroke. Vaspin, apelin, and visfatin play important roles in the regulation of vascular disorders. Our aim was to evaluate whether the concentrations of vaspin, apelin, and visfatin were associated with stroke risk. A total of 235 patients with stroke (156 patients with ischemic stroke and 79 patients with hemorrhagic stroke) and 235 age- and gender-matched healthy controls were included in this study. A sandwich ELISA was developed to measure the serum vaspin, apelin, and visfatin levels. There was a statistically significant difference in the median levels of serum vaspin, apelin, and visfatin levels between stroke cases and controls (vaspin: 1.50 vs 1.07 ng/ml; apelin: 1.56 vs 1.32 pg/ml; visfatin: 23.40 vs 19.65 ng/ml; all P values <.001). Multiple logistic regression analysis showed that, serum vaspin and visfatin levels were significantly inversely associated with increased risk of stroke, and the odds ratios (ORs) in the highest tertile were 2.25 [95% confidence interval (CI) 1.38–3.67; P for trend <.001] for vaspin and 2.56 (95% CI 1.46–4.47; P for trend <.001) for visfatin, respectively, compared with the lowest tertile. Higher apelin levels were marginally associated with lower stroke risk ( P for trend =.060). Our study indicated that higher vaspin, apelin, and visfatin levels might be associated with increased stroke risk. Necessary prospective cohort studies should be conducted to confirm this association in the future.